2016
DOI: 10.1101/073650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Five years investigation of female and male genotypes in Périgord black truffle (Tuber melanosporumVittad.) revealed contrasted reproduction strategies

Abstract: Summary 22The Périgord black truffle (Tuber melanosporum Vittad.) is a heterothallic ascomycete that 23 establishes ectomycorrhizal symbiosis with trees and shrubs. Small-scale genetic structures of 24 female genotypes in truffle orchards are known, but it has not yet been studied in male 25 genotypes. In this study, our aim was to characterize the small-scale genetic structure of both 26 male and female genotypes over five years in an orchard to better understand the T. suggesting an important turnover due to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(49 citation statements)
references
References 40 publications
6
41
1
1
Order By: Relevance
“…S5). This result confirms that also in T. borchii a single mating type tends to dominate in a single soil patch, as found for T. melanosporum and T. aestivum in natural and cultivated truffle ground, and confirms that in field conditions only one strain or multiple strains of the same mating type tend to colonize one single plant (Rubini et al ., ; Linde and Selmes, ; Zampieri et al ., ; Murat et al ., ; Rubini et al ., ; Molinier et al ., ; De la Varga et al ., ). This can be explained by considering that a vegetative incompatibility (VI) system exists in T. borchii , which prevents hyphal interactions between hyphae of different strains (Sbrana et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…S5). This result confirms that also in T. borchii a single mating type tends to dominate in a single soil patch, as found for T. melanosporum and T. aestivum in natural and cultivated truffle ground, and confirms that in field conditions only one strain or multiple strains of the same mating type tend to colonize one single plant (Rubini et al ., ; Linde and Selmes, ; Zampieri et al ., ; Murat et al ., ; Rubini et al ., ; Molinier et al ., ; De la Varga et al ., ). This can be explained by considering that a vegetative incompatibility (VI) system exists in T. borchii , which prevents hyphal interactions between hyphae of different strains (Sbrana et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Several works demonstrated that in Tuber species the maternal tissue of ascomata and surrounding ECMs have the same genotype (Rubini et al ., , Murat et al ., ; Molinier et al ., ; Taschen et al . ; De la Varga et al ., ). Moreover, a physical and nutritional link between these fungal structures has been proved (Le Tacon et al ., ; Deveau et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations